The Effect Of Financial Distress And Liquidity On Audit Report Lag - Suherni; Juardi (Summa : Journal of Accounting and Tax, 2023)
This study aims to determine the effect of Financial Distress and Liquidity on Audit Report Lag. The sample used in this study is the Property and Real Estate that is listed on the Indonesia Stock Exchange (IDX) and published Financial Statements successively in the 2019-2021 period with 46 sample companies. The independent variables of this research are Financial Distress measured by the Z Score (Dummy) and Liquidity measured by the Current Ratio. The dependent variable of this study is the Audit Report Lag as measured by Dummy. Samples were taken using a purposive sampling method with certain criteria, during the research period. The analytical method used is Logistic Regression which is called Report Lag. processed using SPSS 22. The results of this study indicate that Financial Distress does not affect Audit Report Lag while Liquidity has a negative and significant effect on Audit Report Lag.